Computation Takes Time, But How Much? - WILHELM, REINHARD; GRUND, DANIEL (Communications of the ACM, 2014)
The article discusses research attempting to determine how much time computation takes. The authors argue that reliable information on the execution times of all computational tasks involved is the basis for verifying the timeliness of system reactions, noting that worst-case execution-time (WCET) analysis is used to determine such information. Topics include an approximation, called the timing schema method, why compilers and progress in computer architecture render the timing schema method impractical, infeasible, or imprecise, and the objective and main challenges of subtasks in a quasi-standard computer architecture for static timing analysis.